THE SIGNIFICANCE OF UZBEK MOSAIC IN THE URBAN ENVIRONMENT - Xudoyberganov Rustam Adambayevich (American Journals, 2025)
"Street art" is a form of majestic art, realized in many ways, creating art, serving to decorate the urban environment, mosaic, urban planning, education, taste and spirit of society.
Keywords: Mosaic, city, building, street art, monumental, panel.